If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 4(a + -2) = 2(a + -7) + 1 Reorder the terms: 5 + 4(-2 + a) = 2(a + -7) + 1 5 + (-2 * 4 + a * 4) = 2(a + -7) + 1 5 + (-8 + 4a) = 2(a + -7) + 1 Combine like terms: 5 + -8 = -3 -3 + 4a = 2(a + -7) + 1 Reorder the terms: -3 + 4a = 2(-7 + a) + 1 -3 + 4a = (-7 * 2 + a * 2) + 1 -3 + 4a = (-14 + 2a) + 1 Reorder the terms: -3 + 4a = -14 + 1 + 2a Combine like terms: -14 + 1 = -13 -3 + 4a = -13 + 2a Solving -3 + 4a = -13 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -3 + 4a + -2a = -13 + 2a + -2a Combine like terms: 4a + -2a = 2a -3 + 2a = -13 + 2a + -2a Combine like terms: 2a + -2a = 0 -3 + 2a = -13 + 0 -3 + 2a = -13 Add '3' to each side of the equation. -3 + 3 + 2a = -13 + 3 Combine like terms: -3 + 3 = 0 0 + 2a = -13 + 3 2a = -13 + 3 Combine like terms: -13 + 3 = -10 2a = -10 Divide each side by '2'. a = -5 Simplifying a = -5
| 21-8k=-7(2k+3) | | -6x-18=-114 | | 2(-1-2x)+7x=6-5x | | 4x-1=2x-2 | | 66=24x+6y | | 10x+x+-6x=226 | | 5p+5-7=80 | | -9z-3z=-2z-3-4z | | 4c-2/5=6 | | 4(y+9)=3Y-14 | | (x^4)-(8x^2)-20=0 | | 9x-3x+90=9x+48 | | y=2(6+1)+5(3+3) | | 50x^2-288y^10=0 | | 8y-3=6y-17 | | x/4+9=6 | | (9x-23)+(5x+13)=x | | 10x+-6x=226 | | 3(-2/5)= | | (5+4n+2m)+(-6m-8)= | | 6(4x-6)=3(8x+4) | | 3x-3x+18=1 | | 3(.66666667x-2)+x=3 | | 6p=p-32 | | 2(b+13)=-5b/3 | | 5-x^2-43=18 | | 240+.15x=378 | | 4x+10=2x+6 | | 12x-3=36x+15 | | -12x-159=82+3x | | 7+3m-3=6m+10-2m | | 2x-4=5x+14 |